ALTRUISM AS A VALUE AND VIRTUE (International conference on multidisciplinary science, 2025)
This article explores the essence of the concept of altruism and its manifestation as a human value and virtue. Furthermore, it discusses the impact of altruism on social relations and methods of fostering it in the educational process. The study aims to explain the role of altruism in personal development and societal progress.